New records of Heliopora hiberniana from SE Asia and the Central Indian Ocean - Richards, Zoe; Haines, Leon; Scaps, Patrick; Ader, Denis (2020)
Coral reefs are among the most diverse ecosystems on the planet. They provide spawning sites for fishes and habitat for a myriad of fauna and flora. They protect coastlines from waves and storms and have important socio-economic value. However, coral reefs, as we know them, are seriously threatened by globalization and climate change [1]. The widespread bleaching of scleractinian corals threatens to destabilize critical ecosystem functions such as reef-building [2], and a growing body of data indicates that coral reefs are being transformed [3,4]. Future reefs are predicted to be dominated by non-constructional taxa [5,6], and the retreat of scleractinians threatens to cripple coral reef ecosystem functioning and endanger the lives of the millions of people that rely on coral reefs for protection, income and nutrition [7]. To detect coral community responses to climate change, and to identify which species may perform critical functional roles on future reefs, accurate taxonomic and systematic information is needed.